Bleeding pneumonia: Diffuse alveolar hemorrhage due to human metapneumovirus. (2020) - Rodriguez-Nava, Guillermo; Shrestha, Ekta; Upadhyay, Binayak; Morante, Aldo; Joseph, Deepa; Suhail, Aimen; Trelles-Garcia, Daniela Patricia; Yanez-Bello, Maria Adriana
Abstract: Diffuse alveolar hemorrhage is a condition with high morbidity and mortality. The majority of cases are caused by pulmonary capillaritis associated with systemic vasculitis. Infection disease has also been associated with this condition. A 62-year-old woman with a history of chronic alcohol abuse presented with shortness of breath, hemoptysis, constipation, and icterus. Chest x-rays on admission showed diffuse patchy opacities concerning for diffuse alveolar hemorrhage. The patient quickly developed acute respiratory failure requiring intubation. PCR identified human metapneumovirus and bronchoalveolar lavage confirmed alveolar hemorrhage. Despite all efforts, the patient ultimately developed multi-organ failure and died. Human metapneumovirus is usually associated with mild upper and lower respiratory tract infections in young children. Nevertheless, clinicians should recognize that this virus has recently emerged as a significant pathogen, particularly in adult patients with underlying conditions and the elderly population.